Power ranking of the members of the Agricultural Committee of the European Parliament - Imre Fertő; László Á. Kóczy; Attila Kovács; Balázs R. Sziklai (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2021)
We aim to identify the most influential members of the Agricultural Committee of the European Parliament (COMAGRI). Unlike previous studies that were based on case studies or interviews with stakeholders, we analyse the voting power of MEPs using a spatial Banzhaf power index. We identify critical members: members whose votes are necessary to form winning coalitions. We found that rapporteurs, EP group coordinators and MEPs from countries with high relative Committee representations, such as Ireland, Poland or Romania are powerful actors. Italy emerges as the most influential member state, while France seems surprisingly weak.
Keywords: D71; D72; Q18; 330; European Parliament; Common Agricultural Policy; voting games; Banzhaf index; voting game over a convex geometry